The meanings selected Rhodes University student-fans of hip-hop make of the gendered scenarios portrayed in designated South African commercial hip-hop music videos - Mtengwa, Tamuka Phumelela Msawenkosi Misheck (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2020)
Hip-hop is frequently linked to misogyny and other forms of violence. This link, in many instances, is often presented outside of a critical understanding of complex underlying societal and gender dynamics. South Africa's high rates of violence against women make it necessary to understand how hip-hop videos interact with society, as hip-hop, in its commercial form, has become a growing music genre in South Africa. Rhodes University, which has a notable student following of hip-hop, has experienced concerning levels of gender-based tensions as evidenced by the rise of the "fallist" movement's #RapeCultureMustFall, #RUReferenceList and the suicide of Khensani Maseko, at the instigation of an alleged incident of rape, perpetrated by her boyfriend and fellow student. It is therefore of interest to investigate how a select group of Rhodes University student-fans of hip-hop make meaning out of selected South African commercial hip-hop music videos. The hip-hop music videos chosen for the study, hence Pitbull Terrier (Die Antwoord), Pearl Thusi (Emtee), Dlala ka yona (L'Tido), All eyes on me (AKA featuring Burna Boy, Da L.E.S and JR) and Ragga Ragga (Gemini Major featuring Casper Nyovest, Riky Rick and Nadia Nakai), were selected on the strength of their popularity and uniquely gendered scenarios. This study draws on qualitative research methods, thus qualitative thematic content analysis, focus group and in-depth interviews. The study establishes that despite gender being a contentious issue at Rhodes University, students make meaning out of the gendered portrayals based on their own experiences, socialisation, cultural values and level of submission to the discourse of hip-hop. This study seeks to understand how selected student-fans of hip-hop read the gendered portrayals of the music videos, based on their own experiences, socialisation, cultural values, and level of submission to the discourse of hip-hop.
Keywords: Hip-hop -- South Africa; Misogyny -- South Africa -- Makhanda; Rap (Music) -- South Africa; Rap (Music) -- Social aspects -- South Africa; Hip-hop -- Influence; Violence in music; Women -- Violence against -- South Africa; Rape culture -- South Africa; Rap music fans-- -- South Africa -- Makhanda; Misogyny in music; #RapeCultureMustFall; #RUReferenceList